If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 2) + 2(3x + 5) = 0 Reorder the terms: 2(2 + 3x) + 2(3x + 5) = 0 (2 * 2 + 3x * 2) + 2(3x + 5) = 0 (4 + 6x) + 2(3x + 5) = 0 Reorder the terms: 4 + 6x + 2(5 + 3x) = 0 4 + 6x + (5 * 2 + 3x * 2) = 0 4 + 6x + (10 + 6x) = 0 Reorder the terms: 4 + 10 + 6x + 6x = 0 Combine like terms: 4 + 10 = 14 14 + 6x + 6x = 0 Combine like terms: 6x + 6x = 12x 14 + 12x = 0 Solving 14 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 12x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 12x = 0 + -14 12x = 0 + -14 Combine like terms: 0 + -14 = -14 12x = -14 Divide each side by '12'. x = -1.166666667 Simplifying x = -1.166666667
| 2x^3-36=x | | -2+5=-23 | | h^2=036 | | 4M-7=-19 | | .27= | | -2/3m-4=25 | | 9(x+ax+10)= | | (x+1)(z+1)=(y-1)(y+6) | | Y=1.65x | | y^2-6y+12=4 | | Xy=-4x+5 | | Xy=-5x+5 | | 10y+4x=63 | | 3y(-4)+2a=-13y+2a | | 4x+(-x)=27 | | -67.5n=-360 | | -72n=-360 | | 5(2(6)-3)=5 | | -82.5n=-360 | | 5(2(5)-3)=5 | | 5(2(4)-3)=5 | | -87.5n=-360 | | 5(2(3)-3)=5 | | -80n=-360 | | 5(2(2)-3)=5 | | 5=3/w-4 | | 5=(3)/(w-4) | | x-6y=65 | | 4x^2+y^2-4y=0 | | sin30=x/108 | | sin(30)=x/108 | | -60n=-360 |